Insulin Polymers in the Plasma of Obese Subjects Are Associated with Elevated Levels of Carbonyl Groups and Are Decreased by (–)-Epicatechin - Rincón Víquez, M. J.; García-Sánchez, J. R.; Tapia González, M. A.; Gutiérrez López, L.; Ceballos-Reyes, G. M.; Olivares-Corichi, I. M. (Hormone and Metabolic Research, 2014)
We investigated whether oxidative damage and insulin polymerization at a systemic level are associated with the insulin resistance (IR) observed in obese subjects. We evaluated 3 groups (n=16/each) divided according to body mass index (BMI): Normal weight (NW) with a BMI of 18.5–24.9, obese 1 (O1) 30–34.9, and obese 3 (O3)>40 kg/m2. IR and oxidative damage status of the groups were established by HOMA value and the analysis of biomarkers of oxidative stress in plasma. Insulin polymers in systemic circulation were detected using an antibody specific coupled to magnetic beads, which were incubated in plasma from the study groups. Analysis of magnetic beads by electrophoresis on polyacrylamide gel and silver stain assessed the presence of insulin polymers. The inhibition of polymers formation was studied by the presence of (–)-epicatechin. We demonstrated that O1 and O3 subjects with IR showed higher oxidative damage to their plasma lipids and proteins than NW subjects. This oxidative damage was associated with the presence of insulin polymers in the plasma of the O1 and O3 subjects. This polymer showed a high concentration of carbonyl groups by Western blot, suggesting the participation of oxidative damage in the generation of the polymer. The antioxidant (–)-epicatechin decreased the formation of the insulin polymer, indicating that the prevention of oxidative damage can inhibit insulin polymerization. Our study revealed an association between the presence of carbonyl stress, IR, and insulin polymer formation in obese subjects. This study also demonstrates that the antioxidant (–)-epicatechin inhibits insulin polymerization.
Keywords: oxidative damage; insulin resistance; body mass index